Glucagon‐like peptide‐1: modulator of β‐cell dysfunction and death. (4th September 2013) - Rondas, D.; D'Hertog, W.; Overbergh, L.; Mathieu, C.
Abstract: Glucagon‐like peptide‐1 (GLP‐1) is one of the hormones responsible for the incretin effect, a term that refers to the observation that orally administered glucose results in a larger increase in plasma insulin levels and insulin‐dependent decrease in blood glucose concentration when compared to the same amount of glucose given intravenously. GLP‐1 is secreted mainly by gut endocrine L‐cells and is released under the control of carbohydrates, proteins and lipids. Upon secretion, GLP‐1 targets different cell types and exerts a wide variety of actions such as potentiation of glucose‐stimulated insulin secretion, reduction of appetite, delay of gastric emptying and increase in β‐cell mass. These beneficial effects have resulted in the application of GLP‐1‐based therapies in patients with type 2 diabetes, but also exploitation of its effects in type 1 diabetes is being envisaged. In this review, we focus on the different, short‐ and long‐term action mechanisms of GLP‐1 with specific emphasis on its role as a modulator of β‐cell function and survival.